ANALISIS PENGARUH KOMPENSASI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Survei pada Karyawan CV Maju Abadi Garment di Sukoharjo) - Sunarso, Kurnia Wijianti, Alwi Suddin & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The purpose of this study to determine the significance of the effect ofcompensation, motivation and discipline of work on employee performance CV MajuAbadi Garment and dominant variable influence on employee performance CV MajuAbadi Garment. This study used a survey method. Types of data used are qualitative andquantitative data source in the form of primary and secondary data. The technique ofcollecting data through observation, interviews and questionnaires. The population inthis study are employees CV Maju Abadi Garment advanced as much as 311 employees.The sampling technique using proportional random sampling method were 81respondents. Data were analyzed using classical assumption test, multiple linearregression analysis, t-test, F and coefficient of determination. Based on that conclusion,compensation, motivation, and discipline significant effect on employee performance CVMaju Abadi Garment and compensation is the dominant variable influence on employeeperformance CV Maju Abadi Garment.Keywords: compensation, motivation, discipline work, employee performance